Prevalence and antimicrobial resistance of Salmonella isolated from bovine and ovine samples in slaughterhouses of Algiers, Algeria - NOUICHI, S.; OUATOUAT, R.; CAN, H. Y.; MEZALI, L.; BELKADER, C.; OUAR- KORICHI, M.; BERTRAND, S.; CANTEKIN, Z.; HAMDI, T. Y. (Journal of the Hellenic Veterinary Medical Society, 2018)
The aims of our work are to estimate the prevalence of Salmonella isolated from carcasses and feces of cattle and sheep in the two biggest slaughterhouses in Algiers, Algeria, and to characterize the obtained strains by serotyping and antimicrobial resistance testing. The detection of Salmonella was performed by the conventional culture method and isolates were confirmed by PCR. Susceptibility to antibiotics was carried out by agar disc diffusion method. The results showed that 10.17% of samples were Salmonella positive. Carcass samples were more contaminated than fecal samples. Serotyping of the 84 Salmonella isolates has enabled to identify 10 different serovars; the most predominant was S. Muenster. The invA gene was detected in 96.43% of isolates whereas all S. Typhimurium strains were positive for spy gene. Sixty-eight (80.95%) isolates were resistant to at least one of the 28 antibiotics tested and exhibited 17 different antimicrobial resistance patterns. The most frequently observed resistance was to streptomycin (69.05%). While 22.62 % of the isolates were MDR, two S. Typhimurium showed an‘‘ACSSuT’’ pentaresistance pattern. Considering the importance of this group of bacteria for public health, Salmonella control is necessary at several steps of food production to ensure safe products for consumers.